Investigative methodology in the learning of chemical concepts: developing argumentation and Scientific Literacy (Research, Society and Development, 2022)
This research aimed to promote Scientific Literacy (CA) from investigative activities on Chemical Reactions for high school students in the subject of Chemistry, enabling the verification of how the SEI will reach the students during the learning process. Thus, providing the argumentation of chemical concepts, thus being able to identify and analyze the scientific arguments of students through SEI and relate them to CA. A didactic sequence that approaches the investigative methodology aims for the student to be the center of the learning process, thus developing a more critical being that can question and reflect on certain situations, identifying facts and not only accepting them. From these developed abilities arguments are obtained, which will present how the subject thinks about the proposed fact, what his ideas and solutions about this situation are. With this in mind, an SEI was applied to 12 students in a workshop consisting of 5 meetings made up of two investigations with the objective of identifying the development of the students' argumentation. Then, recordings and interviews were used as collection tools for later content analysis. The arguments collected have characteristics that are based on components present in one or more categories, such as, for example, the category "Deduction". Thus, this analysis enabled the understanding of the construction of arguments and the identification of CA indicators. Therefore, the results expose how an SEI can influence the students' arguments and collaborate towards CA, thus reaching the objectives of Basic Education.